2008
DOI: 10.4314/ajtcam.v5i3.31277
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects Of Three Tropical Plant Extracts On <I>Staphylococcus aureus, Escherichia coli and Candida albicans</I>

Abstract: Antimicrobial activities of the leaf extracts of Cymbopogon citatrus (lemongrass) and Vernonia amygdalina (bitter leaf) and the seed extracts of Garcinia kola (bitter kola) were carried out. G. kola had effect only on Staphylococcus aureus and Escherichia coli with no inhibition on Candida albicans. Ethanol, cold water and hot water extracts of Vernonia amygdalina and Cymbopogon citratus showed inhibition on the three organism but G. kola ethanol, cold water and hot water extracts only inhibited S. aureus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 8 publications
3
27
0
4
Order By: Relevance
“…The excellent activity of the plant on bacteria and fungal species shows a very good potential of V. amygdalina to treat diseases caused by pathogens. Okigbo and Mmeka (2008) also reported the antibacterial and antifungal activity of V. amygdalina extracts on S. aureus, E. coli and Candida albicans. These local ethnomedical preparations and prescriptions of plant sources should be scientifically evaluated and disseminated properly.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent activity of the plant on bacteria and fungal species shows a very good potential of V. amygdalina to treat diseases caused by pathogens. Okigbo and Mmeka (2008) also reported the antibacterial and antifungal activity of V. amygdalina extracts on S. aureus, E. coli and Candida albicans. These local ethnomedical preparations and prescriptions of plant sources should be scientifically evaluated and disseminated properly.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of different extracts have shown antioxidant (Igile et al, 1994;Farombi, Owoeye, 2011), antimicrobial (Erasto, Grierson, Afolayan, 2006;Okigbo, Mmeka, 2008), antiparasitic (Tadesse et al, 1993;Ademola, Eloff, 2011;Adiukwu, Amon, Nambatya, 2011), antidiabetic (Akinola et al, 2011;Ong et al, 2011) and antihypertensive (Ajibola, Eleyinmi, Aluko, 2011;Saliu et al, 2011) properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ebenfalls seit Langem bewährt bei dieser Indikation ist Teebaumöl, das unverdünnt auf die betroffenen Hautstellen getupft werden kann. Gleichfalls antimykotisch und antibakteriell wirken die ätherischen Öle von Lemongras (Zitronengras) und Zimtrinde [7,8], die pur oder gelöst in einem fetten Öl angewendet werden. …”
Section: äTherische öLeunclassified